Project Food Aid: Tool for Rural Development? - Ice, Mark E. (Tufts Archival Research Center, 2005)
Volume 11, Issue 2. Summer Properly utilized, project food aid has a legitimate role to play in development programming. Yet, because its budgetary costs are largely hidden and its rhetoric is so overtly humanitarian, it has been embraced uncritically and used indiscriminately. Evaluation has concentrated on the achievement of immediate, specific goals, such as the construction of a school or an irrigation canal. The author draws upon extensive field experience as a relief program administrator and a review of recent writings to assess the broader impacts of project food aid upon the complex socioeconomic environment of entire communities. In contrast to normal expectations, a feeding program can lead to a degraded nutritional status within the target group; an irrigation canal built by Food for Work can leave its rural laborers relatively worse off. These and other paradoxes are explored. In concluding, the author identifies some key considerations for improving the effectiveness and curbing the dangers of project food aid.